Elucidation of the state of water in hydrogels - Demircan, Erhan (My University, 2006)
HİDROJELLER İÇERİSİNDEKİ SUYUN YAPISININ AYDINLATILMASI Hidrojeller içerisindeki suyun yapısının aydınlatılmasında yüksek hassasiyetle izlenebilmesi amacı ile floresans tekniği kullanılmıştır. Özel ESIPT reaksiyonları gerçekleştiren ve bunun sonucu olarak belirgin çift band yayılımı oluşturan 3-HF türevleri, 2-hidroksi-asetofenon ve paraformaldehit reaksiyonundan yola çıkılarak sentezlenmiştir. Son aşamada, flavon molekülün, hidrojel içerisine dahil edilebilmesi amacıyla yapıya akrilamid takılmış ve metil iyodür ile kuaternize edilmiştir. Sentezlenen ürünlerin saflıkları ve reaksiyonlardaki değişimler TLC (İnce Tabaka Kromatografisi), 1H-NMR (Proton Nükleer Magnetik Rezonans) ve MASS (kütle spektroskopisi) kullanılarak kontrol edilmiştir. Hidrojeller içerisindeki suyun yapısının aydınlatılması amacı ile floresans veren 3-HF (prob) içeren Polivinilpirolidon (PVP) polimeri sentezlenmiş ve floresans spektroskopisi tekniği ile ölçümler alınmıştır. Absorpsiyonlardaki değişimler ve 3-HF lerin farklı polaritelerdeki floresans özellikleri izlenmiştir. Farklı polarite ortamları, çözeltiye su ilave edilerek oluşturulmuştur. Düzenli su eklenmesi ile oluşan düzenli floresans değişimleri, hidrojeller içerisindeki bağlı ve serbest su miktarlarının hesaplanabileceği bu çalışma ile işaret edilmektedir. i

ELUCIDATION OF THE STATE OF WATER IN HYDROGELS The fluorescence technique is employed for the elucidation of the state of the water in the hydrogels in high-level sensitivity. The 3-HF derivatives, that undergo ESIPT reactions have been synthesized from the reaction of 2-hydroxy acetophenon and paraformaldehyde. To include the flovane molecule into the hydrogel, acrylamide has been fitted to the structure and quaternized with methyl iodide. The purity of the synthesized products and the changes in the reactions have been controled by TLC (Thin Layer Chromotography), 1H-NMR (Proton Nuclear Magnetic Resonance) and Mass Spectroscopy. Polyvinyl pyrrolidone including 3-HF (probe) has been synthesized and fluorescence spectroscopic measurements have been performed. The changes in the absorption and the fluorescence properties of the 3-HFs at different polarities have been studied. Different polarity environments have been constituted by adding water into the solution. The results obained from this thesis indicate that the amount of bonded and free water in hydrogels may probably be determined using the response of two characteristic fluorescence emission peaks to changes in water content. Key words: Hydrogel, fluorescence probe, ESIPT, 3-hydroxy flavone.
Keywords: Hidrojel; Kimya